# Are this two sentences equivalent?

I have a sentence in natural language: "the sum has a neutral element and it is unique", which I have to write in a first order language that has a binary relationship symbol of equality $$='$$ and a binary function symbol $$f_1$$ which represents the sum. We were told not to bother with left and right identity, just check one. So what I did is:

$$(\exists x_i)(\forall x_j)f_1(x_i,x_j) =' x_j \land (\forall x_k)( (\forall x_j)f_1(x_i,x_j) =' x_j \to (x_i =' x_k)).$$

Someone in the class came up with this other one which looks equivalent but at the same time, it doesn't seem to say the same (which of course it makes no sense, is either equivalent and it says the same or its not equivalent):

$$(\exists x_i)(\forall x_j)(f_1(x_i,x_j) =' x_j \land (\forall x_k)(f_1(x_k,x_j) =' x_j \to (x_i =' x_k))).$$

Notice that now every occurrence of $$x_j$$ is under the influence of the same quantifier. So my understanding is that I can change the order of the $$(\forall x_k)(\forall x_j)$$ in my formula and then apply that universal quantifier distributes over conjunction, and I get his formula, and so they are equivalent. Is that correct?

And of course, if there's something wrong with my formula, please do point it out.

Edit

As ryang pointed out, there is a problem in my formula, since only the first occurrence of $$x_i$$ is under the influence of the existential quantifier. Reading it again, I noticed another typo, where it says $$x_i$$ instead of $$x_k$$. So, the corrected version of my formula is:

$$(\exists x_i)((\forall x_j)f_1(x_i,x_j) =' x_j \land (\forall x_k)( (\forall x_j)f_1(x_k,x_j) =' x_j \to (x_i =' x_k))).$$

$$(\exists x_i)(\forall x_j)f_1(x_i,x_j) =' x_j \land (\forall x_k)( (\forall x_j)f_1(x_i,x_j) =' x_j \to (x_i =' x_k))$$

$$(\exists x_i)(\forall x_j)(f_1(x_i,x_j) =' x_j \land (\forall x_k)(f_1(x_k,x_j) =' x_j \to (x_i =' x_k)))$$

Since the variable $$x_i$$ is free in the first but not the second formula, the formulae aren't equivalent.

To analyse just their logical form, your two formulae can be more readably rewritten: $$\begin{gather}∃x∀y\; Pxyy \quad∧\quad ∀z\; (∀y\; Pxyy \to Qxz)\tag1\\∃x∀y\; \Big(Pxyy \quad∧\quad ∀z\;(Pzyy \to Qxz)\Big).\tag2\end{gather}$$ For easier comparison, here's a logical rewrite: $$\begin{gather}∃r∀s∀z∃y\; \Big(Prss \quad∧\quad (Pxyy \to Qxz)\Big)\tag1\\∃x∀z∀y\; \Big(Pxyy \quad∧\quad (Pzyy \to Qxz)\Big).\tag2\end{gather}$$

P.S. Note that \begin{align}&∀y\; Pxyy \to Qxz\\\equiv{}& (∀y\; Pxyy) \to Qxz\\\equiv{}& ∃y\;(Pxyy \to Qxz).\end{align}

Addendum (corresponding to the OP's Edit)

the corrected version of my formula is: $$(\exists x_i)((\forall x_j)f_1(x_i,x_j) =' x_j \land (\forall x_k)( (\forall x_j)f_1(x_k,x_j) =' x_j \to (x_i =' x_k)))$$

Considering its logical form: $$∃x\;\Big(∀y\; Pxyy \quad∧\quad ∀z\; (∀y\; Pzyy \to Qxz)\Big).\tag{1r}$$

Logical rewrite: $$∃x∀s∀z∃y\; \Big(Pxss \quad∧\quad (Pzyy \to Qxz)\Big).\tag{1r}$$

Unfortunately, $$∃x∀z∀y\; \Big(Pxyy \quad∧\quad (Pzyy \to Qxz)\Big)\tag2$$ (duplicated from above) is logically equivalent to neither $$(1)$$ nor $$(1r).$$

• Thank you for you answer. I see! I think that is a mistake in my formula, right? That xi shouldn't be free. I love the first rewrite, it's super clear.
– lbal
May 20 at 17:44
• I added a corrected version of my formula. Thanks for pointing that out!
– lbal
May 20 at 18:27
• That's actually somehow a relief, because I was buffled by the idea of the two formulas being equivalent. I now (thanks to the rewrite) understand how they are different. The second one is stronger, and its definitely not what we are trying to say. I appreciate very much your answer.
– lbal
May 20 at 20:00
• @lbal You're welcome! "The second one is stronger" Yep: $(2)$ entails $(1\text r)$ but not vice versa. May 20 at 20:47

Yes you can change the order of two(or more) adjacent "for every" quantifiers, and yes, the quantifier can distribute over the conjunction, the real question is where to put the brackets, and this depends not only on the meaning of the sentence, but also on the meaning of the brackets, the convention I believe is that when a quantifier is in a bracket, it extends only to those statements within that bracket (unless you use them like here where every quantifier is alone in a pair of brackets, then it is reasonable to assume that they apply to the brackets adjacent to them)

So in short, yes the two statements are equivalent if you bracket them correctly